2007
DOI: 10.1016/j.bpc.2007.05.007
|View full text |Cite
|
Sign up to set email alerts
|

The solubilisation pattern of lutein, zeaxanthin, canthaxanthin and β-carotene differ characteristically in liposomes, liver microsomes and retinal epithelial cells

Abstract: The incorporation efficiencies of lutein, zeaxanthin, canthaxanthin and beta-carotene into Retinal Pigment Epithelial (RPE) cells (the human RPE cell line D 407), liver microsomes and EYPC liposomes are investigated. In RPE cells the efficiency ratio of lutein and zeaxanthin compared to canthaxanthin and beta-carotene is higher than in the other membranes. The preferential interactions of lutein and zeaxanthin with RPE cells are discussed considering special protein binding properties. Incorporation yields wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Lipid bilayers have attracted much interest as idealized model systems for cellular membranes mainly because many of their physical properties are close to those of natural membranes [58]. Although it was shown that the incorporation efficiencies of lutein, zeaxanthin and canthaxanthin into different types of membranes are different and the conclusion drawn that neither liposomes nor microsomes may be considered model for studies of the incorporation of carotenoids into retinal pigment epithelial (RPE) cells [59], only model studies on defined membranes can give insight into the molecular interactions between these pigments and the membrane lipids.…”
Section: Mechanisms Of Canthaxanthin Delivery To the Macula Lutea Memmentioning
confidence: 99%
“…Lipid bilayers have attracted much interest as idealized model systems for cellular membranes mainly because many of their physical properties are close to those of natural membranes [58]. Although it was shown that the incorporation efficiencies of lutein, zeaxanthin and canthaxanthin into different types of membranes are different and the conclusion drawn that neither liposomes nor microsomes may be considered model for studies of the incorporation of carotenoids into retinal pigment epithelial (RPE) cells [59], only model studies on defined membranes can give insight into the molecular interactions between these pigments and the membrane lipids.…”
Section: Mechanisms Of Canthaxanthin Delivery To the Macula Lutea Memmentioning
confidence: 99%
“…galloxanthin [19]; 1-carotene [9]; zeaxanthin [20,21]; and astaxanthin [9,22]. We also calculated the absorptance, A(l), connected to various peak absorbance values, D max , for an object containing galloxanthin, zeaxanthin or astaxanthin.…”
Section: Materials and Methods (A) Optical Parameters Of The Oil Dropletsmentioning
confidence: 99%
“…The resulting carotenoid solution in chloroform (5 ml) was evaporated on a rotary evaporator to a volume of 1 ml. Liposomes with carotenoids were obtained by the method given in the article by Shafaa et al (43) with slight changes. 100 μl of chloroform solution (20 mg/ml) of egg phosphatidylcholine (Avanti) was added to carotenoid solution in chloroform (1 ml), stirred and evaporated chloroform on a rotary evaporator.…”
Section: Production Of Liposomes With Carotenoidsmentioning
confidence: 99%